Rhizospheric iron and arsenic bacteria affected by water regime: Implications for metalloid uptake by rice. (March 2017) - Zecchin, Sarah; Corsini, Anna; Martin, Maria; Romani, Marco; Beone, Gian Maria; Zanchi, Raffaella; Zanzo, Elena; Tenni, Daniele; Fontanella, Maria Chiara; Cavalca, Lucia
Abstract: Rice is characterized by high levels of arsenic accumulation, even if cultivated in non-contaminated soils. Given the limits for arsenic concentration in rice grain recently established by the European Community, it is essential to understand the mechanisms and find solutions to this issue. Arsenic bioavailability is strictly related to water management of the rice paddy as well as to iron- and arsenic-cycling bacterial populations inhabiting the rice rhizosphere. To evaluate the effect of different agronomic conditions on the root-soil microbiota involved in arsenic mobilization, rice plants were grown in macrocosms containing non contaminated field soil under either continuous flooding, aerobic rice regime or continuous flooding with a 14 day-period of drainage before flowering. Specific groups of iron- and arsenic-cycling bacteria were assessed by real time quantitative PCR and fluorescence in situ hybridization. Continuous flooding led to the release of arsenate and iron in soil solution and produced rice grains with arsenite and organic arsenic above the recently established limits, contrary to the other agronomic conditions. Iron-reducing bacteria affiliated to the family Geobacteraceae significantly increased under continuous flooding in rhizosphere soil, in concomitance to arsenate dissolution from iron minerals. The 14 day-period of drainage before flowering allowed the recycling of iron, with the increase of Gallionella -like iron-oxidizing bacteria. This phenomenon likely influenced the decrease of arsenic translocation in rice grains. Regardless of the water regime, genes for arsenite oxidation ( aioA ) were the most abundant arsenic-processing genes, explaining the presence of arsenate in soil solution. The presence of arsenite and organic arsenic in rice grains produced under continuous flooding might be related to the retrieval of genes for arsenate reduction ( arsC ) and for arsenite methylation ( arsM ) in the proximity of the roots. These outcomes indicate a potential active role of rhizospheric iron- and arsenic-cycling bacteria in determining arsenic accumulation in rice grains from plants cultivated under continuous flooding, even in soil with a low arsenic content. Highlights: Iron bacteria influence arsenic solubility. Iron bacteria are affected by water management. Arsenic bacteria influence arsenic speciation in soil solution and in grain. Dissimilatory arsenate reduction is not relevant for arsenic solubilization in rice rhizosphere.